St. Kitts and Nevis : Statistical Appendix. (IMF Staff Country Reports; Country Report ;, 2008)
In this paper, statistical details are listed regarding the following: GDP by sector at constant and current prices, tourism data, indicators of agricultural production, wage rates of workers, number of workers in the social security by age group, retail price index, central government operations and revenue, central government expenditure and domestic debt, operations of social security bond, monetary survey, distribution of commercial bank loans and interest rates, indicators of commercial bank, consolidated balance sheet, and balance of payments.